MORECARE CAPACITY: MENTAL CAPACITY AND PROCESSES OF CONSENT FOR RESEARCH ON END-OF-LIFE CARE. Issue 1 (1st March 2013) - Stone, K; Hotopf, M; Koffman, J; Lewis, P; Wee, B; Bernal, W; Higginson, IJ; Evans, C J
Abstract : Introduction: A major barrier to improving end-of-life care (EoLC) is the inclusion of those near to death in research studies. The Mental Capacity Act 2005 clarified concepts on involving adults lacking capacity in research and there are examples of innovative approaches but uncertainty surrounds best research practice. This paper systematically appraises the evidence on the challenges and solutions for adults lacking capacity to participate in research on EoLC. Aims and Methods: A meta-synthesis of the literature on capacity and consent in research on palliative and EoLC to examine the challenges and solutions and identify best practice. A systematic literature appraisal searching five electronic databases and grey literature email survey. Search terms included consent and capacity (and synonyms) within three patient groups: palliative care, mental health and accident and emergency. Selection criteria: primary research concerning adults with compromised capacity and processes of consent in research. A short-semi structured email survey to leading national and international researchers (n=317) to capture 'out of view' best practice. Results: 9916 references were identified, 107 included for full paper review in the palliative care group. Four main themes were identified: (1) timing, (2) proxies and supportive decision making, (3) research resource and expertise, and (4) ethical consideration. 63% of survey respondents had undertaken research involving adults with compromised capacity with assent being the most common approach used. Conclusions: The meta-synthesis provides guidance on key challenges and solutions to involving those at the end-of-life in research including timing, proxies and supportive decision making, resources for research and ethical considerations.